María Pita in the Theatre. The Dramatic Works of Antonio Valladares de Sotomayor and Francisco Robello y Vasconi - Briante Benítez, Federico Juan (Madrygal. Revista de Estudios Gallegos, 2020)
In this article, we analyze two theatrical texts that deal with María Pitaʼs intervention in the English siege of A Coruña in 1589. One of them is the comedy Defensa de La Coruña por la heroica María Pita, composed by Antonio Valladares de Sotomayor, famous Galician playwright of the eighteenth-century and author of a wide and varied theatrical production. The other text, which had been practically ignored so far, is called María Pita o la heroína de Galicia; we attribute the authorship of this historical drama to Francisco Robello y Vasconi, a nineteenth-century actor of whom we barely had news, hence we have been forced to reconstruct his biography, to the extent that it has been possible. A comparison between Valladaresʼs comedy and Robelloʼs drama reveals differences in various areas, such as the ideological one.
Keywords: A Coruña; María Pita; Theatre; Valladares de Sotomayor; Robello y Vasconi